2017
DOI: 10.3892/etm.2017.5358
|View full text |Cite
|
Sign up to set email alerts
|

Function of miR‑25 in the invasion and metastasis of esophageal squamous carcinoma cells and bioinformatical analysis of the miR-106b-25 cluster

Abstract: Abstract. MicroRNAs (miRNAs/miRs) are a class of small, non-coding RNA molecules that serve a key function in carcinogenesis and tumor progression. Recent evidence indicates that miRNAs may act as powerful regulators of migration and invasion. The present study aimed to investigate the effect of miR-25 on the invasion and metastasis of KYSE-150 and EC109 esophageal squamous cell carcinoma (ESCC) cells, and predict the mechanism of this effect by bioinformatically analyzing the miR-106b-25 cluster. In order to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…It has been reported that miR-106b-3p, miR-455-5p, and miR-128 function as tumor suppressors, and have suppressed EMT or metastasis in ESCC [33,43,44]. While miRNAs, such as miR-543, miR-23b-3p, miR-25, and miR-99b/let-7e/miR-125a play oncogenic roles in promoting EMT or metastasis during ESCC progression [68,70,109,113]. These miRNAs could serve as promising therapeutic targets in ESCC development.…”
Section: Non-coding Rnas and Emt And Metastasis In Esccmentioning
confidence: 99%
“…It has been reported that miR-106b-3p, miR-455-5p, and miR-128 function as tumor suppressors, and have suppressed EMT or metastasis in ESCC [33,43,44]. While miRNAs, such as miR-543, miR-23b-3p, miR-25, and miR-99b/let-7e/miR-125a play oncogenic roles in promoting EMT or metastasis during ESCC progression [68,70,109,113]. These miRNAs could serve as promising therapeutic targets in ESCC development.…”
Section: Non-coding Rnas and Emt And Metastasis In Esccmentioning
confidence: 99%
“…miRNAs are aberrantly expressed in various cancers and function as a novel class of oncogenes or tumor-suppressor genes depending on their targets. MiR-25 was reported to be associated with tumor carcinogenesis and metastasis, including ESCC [6][7][8]. But its exact mechanisms and roles in vivo are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Although a significant difference in transfection efficiency between two CCA cell lines was observed, the difference in biological functions was not proportionally pronounced. Cancer cells exhibit different degrees of differentiation which can produce cells with different morphological and functional features (32). Various molecular pathways regulated by miR-25 have been studied in a number of cancer types.…”
Section: Univariate Analysis Multivariate Analysis ------------------mentioning
confidence: 99%